Ergonomical Evaluation of Manually-Operated Fertilizer Broadcaster with Farm Women - Singh, S P; Gite, L P; Agrawal, Nidhi (Journal of Agricultural Engineering, 2004)
Farm tools and equipments for various agricultural operations have been designed mostly for men workers although women are actively engaged in almost all farming activities for long hours in Indian agriculture. Granular fertilizers in field crops are mostly applied by broadcasting, and this operation is generally done by farm women. To ease the broadcasting work a commercially available fertilizer broadcaster was evaluated with 11 farm women workers to assess its suitability for women workers. It was found from the ergonomicall stUdy that the mean work heart rate and ?HR was 146.7 + 13.3 beats/min and 65.4 + 18.8 beats/min, respectively with full hopper capacity of 9 kg. Higher work heart rate and ?HR indicated the need of refinements in the fertilizer broadcaster to make it suitable for farm women. The effective field capacity and swath with of the broadcaster was found to be 1.15 ha/h and 5 m, respectively. Based on the ergonomical study, anthropometrical data and feedback received from the subjects, the refinement in the hopper capacity, total height of broadcaster, height of crank handle, cushioning on back portion etc. was proposed.